Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1159/000149072
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Isolations from Cell Cultures of Human Adenocarcmomas of the Colon

Abstract: Cytomegalovirus was isolated from cell cultures derived from 3 of 16 surgical specimens of adenocarcinomas of the colon. Virus identification was accomplished through electron microscopical, cytochemical, and immunofluorescent procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…[14][15][16][17][24][25][26][27] CMV has been associated with several specific human malignancies including carcinomas of the cervix, [28][29][30][31][32] prostate, [33][34][35][36] and colon. [37][38][39] However, a number of conflicting reports have either failed to show evidence of an association with CMV or have questioned the significance of the presence of CMV in these particular tumors. [40][41][42][43][44][45] There is relatively little information in the literature pertaining to CMV and brain neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][24][25][26][27] CMV has been associated with several specific human malignancies including carcinomas of the cervix, [28][29][30][31][32] prostate, [33][34][35][36] and colon. [37][38][39] However, a number of conflicting reports have either failed to show evidence of an association with CMV or have questioned the significance of the presence of CMV in these particular tumors. [40][41][42][43][44][45] There is relatively little information in the literature pertaining to CMV and brain neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus has been isolated from surgical specimens of colonic adenocarcinomas (Hashiro, Horikami & Loh, 1979) and CMV DNA has been reported to be detectable using whole virus genomic material (Huang & Roche, 1978). In contrast, Hart, Neill & Norval (1982) could find no association between CMV and carcinoma of the colon using in situ hybridization and explant techniques.…”
Section: Colonic Carcinomamentioning
confidence: 99%
“…The presence of HCMV antigens and genome in colorectal cancers has been obtained by means of molecular studies and a direct relationship between the virus and cancer was suggested [8][9][10][11][12]. The possible association of CMV with human colorectal adenocarcinomas was reported first by Huang and Roche [8] who detected CMV DNA in 4 of 7 colonic adenocarcinomas by membrane complementary RNA-DNA hybridization.…”
Section: Discussionmentioning
confidence: 99%
“…So far, studies have provided contradictory results. Some authors were able to detect CMV DNA in colorectal adenocarcinomas by different laboratorial techniques, such as in situ hybridization and PCR [8][9][10][11][12]. In contrast, others failed to demonstrate the presence of CMV in tissue samples of colorectal cancer, even using the same methods of detection [7,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%